Finite Element Analysis of the Displacement Adjustment Scheme for Column Bases of a 10000 m3 Spherical Tank During Whole-body Heat Treatment. (2015) - Yao, Z.Y.; Wu, X.H.; Chen, Y.D.; Jiang, H.F.; Li, Y.T.
Abstract: The stress of spherical tank and displacement of column bases were calculated by finite element method, considering the uneven gravity loads on support columns which was caused by manufacturing and setting errors. The preliminary displacement adjustment scheme for column bases was made, according to the safety range of column bases displacement which was determined by the maximum stress restricted by allowable stress at the set heat treatment temperatures. The final scheme was made after checking the preliminary scheme. The method of making adjustment scheme of column bases for a 10000m 3 spherical tank during the whole-body heat treatment may provide a reference for other large spherical tank.